Powszechność i partykularyzm - przechyły terytorialne w wyborach sejmikowych 2006-2014 = Ubiquity and particularism - territorial shifts in the elections for polish regional assemblies between 2006 and 2014 - Flis, Jarosław; Stolicki, Dariusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to analyse the territorial polarization of rivalry in the elections for Polish regional assemblies (sejmiks) between 2006 and 2014. The authors compared the support for electoral committees in the counties (powiats) showing higher and the counties showing lower than the average for a whole province (wojewodztwo) results. The study covered all Polish provinces. To perform the study, the authors used the indicator of territorial shifts.
Keywords: wybory do sejmików; polaryzacja terytorialna; geografia wyborcza; wskaźnik przechylenia; elections for Polish regional assemblies; territorial polarization; electoral geography; indicator of shift